Evaluation of the usability of patients attended in gastrointestinal telemedicine postpandemic at University clinic - Castro, Lorena (2024)
Telemedicine has grown during the COVID-19 pandemic. Gastroenterology at Clínica Universidad de los Andes has continued it post-pandemic. Usability is the measure by which users evaluate the effectiveness, efficiency, and satisfaction in telemedicine. The usability of this type of consultation in Chile is unknown. Objective: To evaluate the level of usability among patients attended through teleconsultations in Gastroenterology at Clínica Universidad de los Andes (March-August 2023). Materials and methods: A cross-sectional descriptive study on the level of usability using the adapted and modified Telehealth Usability Questionnaire. It consists of 12 items (score range 12-84) and comprises 2 factors: effectiveness and ease of use. Sociodemographic characteristics were also evaluated. Results: A total of 150 questionnaires were analyzed. A high level of usability was observed (median: 81; range 54-84), with high scores in effectiveness (median: 28; range 20-28) and ease of use (median: 53; range 30-56), without significant differences according to sex, age, educational level, geographic location, and health insurance. Of the respondents, 76.7% were aged 30 to 64 years. 36% resided in the metropolitan region, 61% were women, and 80% were from the private health system. 29% consulted for abdominal pain, 20% for inflammatory bowel disease, and 17% for abnormal liver function tests. For 53.3%, it was their first consultation, and 46.7% were in follow-up via this method. Conclusion: In this cohort, telemedicine is perceived as an effective and easy-to-use tool, with a high level of usability regardless of the patients' sociodemographic characteristics. Therefore, in gastroenterology, telemedicine appears to be a form of healthcare accepted by patients.